2006
DOI: 10.3201/eid1210.060051
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Epidemiology ofPlasmodium vivax, Afghanistan

Abstract: Plasmodium vivax is endemic to many areas of Afghanistan. Geographic analysis helped highlight areas of malaria risk and clarified ecologic risk factors for transmission. Remote sensing enabled development of a risk map, thereby providing a valuable tool to help guide malaria control strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 4 publications
1
65
0
1
Order By: Relevance
“…pulcherrimus is thought to be the main vector in Afghanistan (Brooker et al, 2006). Plasmodium vivax (VK210 and VK247 subtypes) was detected in specimens collected in Afghanistan (Rowland et al, 2002) and P. vivax circumsporozoite proteins were detected though enzyme-linked immunosorbent assay (ELISA) in wild-infected wild-infected mosquitoes (the vast majority of which were An.…”
Section: An Pulcherrimus Theobald No Yesmentioning
confidence: 99%
“…pulcherrimus is thought to be the main vector in Afghanistan (Brooker et al, 2006). Plasmodium vivax (VK210 and VK247 subtypes) was detected in specimens collected in Afghanistan (Rowland et al, 2002) and P. vivax circumsporozoite proteins were detected though enzyme-linked immunosorbent assay (ELISA) in wild-infected wild-infected mosquitoes (the vast majority of which were An.…”
Section: An Pulcherrimus Theobald No Yesmentioning
confidence: 99%
“…NDVI was used to generate risk and distribution maps for diseases with arthropod vectors (Kalluri et al 2007), as well as for temporal models of disease outbreaks (Chretien et al 2007). Malaria and other mosquito-borne diseases such as West Nile virus seem to receive the most frequent attention and be particularly amenable to modeling efforts involving spatiotemporal data such as NDVI, due to the close causal link between rainfall and both mosquito abundance and NDVI (Brooker et al 2006, Gemperli et al 2006, Ceccato et al 2007, Britch et al 2008. But other zoonoses like Hantaan virus (Yan et al 2007), schistosomiasis (Clements et al 2008, Wang et al 2008, Ebola (Pinzon et al 2004a), bubonic plague (Kausrud et al 2007), leishmaniasis (Werneck et al 2007), Rift Valley fever (Anyamba et al 2009) and others have been found to have spatial and/or temporal components associated with NDVI variability.…”
Section: Ndvi: Not Just For Large Herbivoresmentioning
confidence: 99%
“…22,23 Given the wide geographic distribution of respondents, actual malaria exposure during the period was unknown, and varied widely ranging from no risk in the mountainous regions to substantial risks in some of the northern and southeastern regions. 24 This study highlights issues with compliance and side effects experienced by U.S. Army soldiers taking long-term antimalarial chemoprophylaxis, which should be interpreted in light of the study's limitations. Comparison of side effect rates between MQ and doxycycline is challenging, as medication assignment was not random and MQ therapy was generally provided only to those intolerant of doxycycline.…”
Section: Discussionmentioning
confidence: 99%